Trends and characteristics of suicidal ideation among university students in Japan - Ryo Horita; Angelica Silvestre; Taku Fukao; Nanako Imamura; Satoko Tajirika; Miho Adachi; Minako Kawamoto; Mayumi Yamamoto (Cogent Psychology)
Objective Since the number of suicides among university students is relatively high, higher education institutions need to understand the mental health characteristics of university students and work toward suicide prevention. This study aimed to examine the trends of suicidal ideation among Japanese university students as this factor has not been sufficiently clarified.Method The study utilizes the Counseling Center Assessment of Psychological Symptoms-Japanese to assess psychological symptoms among 9,531 students (4,720 female and 4,811 male; 2,896, 2,218, 2,056, and 2,361 first-, second-, third-, and fourth-year students, respectively) over three years, categorizing participants into no suicidal ideation, moderate suicidal ideation, or high suicidal ideation groups based on their suicidal ideation scores.Results The findings reveal that 7.6% of the students were in the high suicide ideation category. The one-way analysis of variance results indicated that higher levels of suicidal ideation were significantly associated with poorer mental health factors such as depression, generalized anxiety, social anxiety, eating concerns, academic distress, family distress, hostility, and alcohol use. The results of chi-square and residual analyses indicated that female students and upper-grade male students were more likely to report higher levels of suicidal ideation.Conclusions This study elucidated the prevalence of suicidal ideation and its association with mental health and demographic factors. Although suicide prevention programs exist in Japan, the findings suggest that early intervention and targeted support, particularly for female students, are crucial when implementing comprehensive mental health care programs.